Bot Innovation Realizing Service Excellence: Designing WhatsApp Chatbot as a Customer Service Solution - Puspitasari, Nia Budi; Ginting, Asteria Noventi Ageta Br; Saribu, Aditya Agung F. Dolok (Jurnal Sistem Informasi Bisnis, 2025)
With the support of qualified employees, PT BPR PPK is a banking company that provides excellent customer service. According to interviews with Bank P employees and customers, customers are dissatisfied with the information they receive. Employees sometimes responded to customer inquiries about Bank P's products and banking within 1 to 2 weeks. Additionally, not everyone can access the website due to a lack of understanding of technology, particularly among older customers. As a result, customers require a more detailed, interactive, and easily accessible information system, mainly through integrating AI technology as a chatbot into the WhatsApp application. This research aims to make it easier for customers to access Bank P's banking information. The chatbot design employs the waterfall method, utilizing dialog flow tools and a decision tree chatbot type that aligns with the user's needs. According to black-box testing results, the chatbot system meets functional needs and follows the database. Meanwhile, the user satisfaction questionnaire yielded an average accuracy of 98.6%, demonstrating the chatbot's feasibility in providing customers with the necessary information. The chatbot system also received a positive response from users.